Stronger together: Developing research partnerships with social impact organizations. Issue 3 (12th April 2022) - Bublitz, Melissa G.; Peracchio, Laura A.; Davis, Brennan; Escalas, Jennifer Edson; Hansen, Jonathan; Miller, Elizabeth G.; Vallen, Beth; White, Tiffany B.
Abstract: A growing number of Transformative Consumer Research (TCR) academic community members are establishing research partnerships with Social Impact Organizations (SIOs) such as nonprofits, public policy entities, and other societally focused organizations and initiatives. These relational engagement partnerships with SIOs are vital for TCR researchers because SIOs have deep connections to people and communities where transformative change takes place. We leverage insights from TCR researchers and SIOs engaged in relational engagement partnerships to outline a framework for such partnerships that supports and sustains these collaborations, furthers knowledge creation, and lays the groundwork for social impact. Our goal is to offer a framework for relational engagement partnerships that can propagate within the TCR community, encouraging fruitful collaborations between TCR researchers and SIOs that have the potential to create positive social impact.